2005
DOI: 10.1002/bies.20312
|View full text |Cite
|
Sign up to set email alerts
|

KASH 'n Karry: The KASH domain family of cargo‐specific cytoskeletal adaptor proteins

Abstract: A diverse family of proteins has been discovered with a small C-terminal KASH domain in common. KASH domain proteins are localized uniquely to the outer nuclear envelope, enabling their cytoplasmic extensions to tether the nucleus to actin filaments or microtubules. KASH domains are targeted to the outer nuclear envelope by SUN domains of inner nuclear envelope proteins. Several KASH protein genes were discovered as mutant alleles in model organisms with defects in developmentally regulated nuclear positioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
197
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(198 citation statements)
references
References 68 publications
(108 reference statements)
1
197
0
Order By: Relevance
“…The klarsicht gene was found to encode a protein with a Cterminal domain shared with ANC-1 of C. elegans and Syne/Nesprin proteins of vertebrates (Starr and Fischer, 2005;Wilhelmsen et al, 2006). This motif was termed the KASH domain for Klarsicht, ANC-1, and Syne homology.…”
Section: Linking the Nucleus To The Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…The klarsicht gene was found to encode a protein with a Cterminal domain shared with ANC-1 of C. elegans and Syne/Nesprin proteins of vertebrates (Starr and Fischer, 2005;Wilhelmsen et al, 2006). This motif was termed the KASH domain for Klarsicht, ANC-1, and Syne homology.…”
Section: Linking the Nucleus To The Cytoskeletonmentioning
confidence: 99%
“…Specifically, mutational screens in yeast (Saccharomyces cervisiae and Schizoscharomyces pombe), filamentous fungi (Aspergillus nidulins and Neurospora crassa), nematodes (Caenorhadbitis elegans), and fruit flies (Drosophila melanogaster) have all implicated microtubule-based motors and specific classes of nuclear envelope proteins as essential for nuclear migration and positioning (Morris, 2003;Xiang and Fischer, 2004;Starr and Fischer, 2005;Wilhelmsen et al, 2006). With regard to cytoskeletal motors, cytoplasmic dynein and dynactin are essential for normal nuclear migration in multiple contexts.…”
Section: Proteins For Movingmentioning
confidence: 99%
“…2; for review see 6,[13][14][15]. In general, SUN proteins contain a conserved SUN domain at their C-termini and at least one transmembrane domain.…”
Section: Kash and Sun Proteins Bridge The Nuclear Envelopementioning
confidence: 99%
“…2; for review see ref. 6,[13][14][15]. The nuclear envelope bridging model has been refined by four groups who have each concluded that SUN proteins reside in the INM where they function to target and retain KASH proteins to the ONM through a direct interaction.…”
Section: Kash and Sun Proteins Bridge The Nuclear Envelopementioning
confidence: 99%
“…Although UNC-83 is essential for nuclear migration in many developmental events, its molecular mechanism and interacting partners remain unknown. UNC-84 is a novel protein with a (Hagan and Yanmagida, 1995;Malone et al, 1999Malone et al, , 2003Hodzic et al, 2004;Padmakumar et al, 2005;Starr and Fischer, 2005). UNC-84 localizes to the nuclear envelope in nearly all somatic cells from the 24-cell stage on in development .…”
mentioning
confidence: 99%